Recent Progress in the Metal-Free or Nonnoble-Metal-Catalyzed Oxidation of Alkynes by Using Pyridine N-Oxides as External Oxidants - Zhou, Bo; Li, Long; Ye, Long-Wu (Synlett, 2016)
Catalytic oxidation of alkynes by using pyridine N-oxides as external oxidants has proven to be a powerful tool in organic synthesis, allowing the assembly of functionalized carbocycles and heterocycles in a remarkably efficient manner. Recent progress in this area is reviewed with emphasis on metal-free or nonnoble-metal-catalyzed oxidative cyclizations.
Keywords: green chemistry; heterocycles; alkynes; oxidation; catalysis